2013
DOI: 10.3174/ajnr.a3536
|View full text |Cite
|
Sign up to set email alerts
|

C-Arm CT Measurement of Cerebral Blood Volume and Cerebral Blood Flow Using a Novel High-Speed Acquisition and a Single Intravenous Contrast Injection

Abstract: BACKGROUND AND PURPOSE: Assessment of perfusion parameters is important in the selection of patients who are most likely to benefit from revascularization after an acute ischemic stroke. The aim of this study was to evaluate the feasibility of measuring cerebral perfusion parameters with the use of a novel high-speed C-arm CT acquisition in conjunction with a single intravenous injection of contrast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 22 publications
1
44
0
Order By: Relevance
“…The time attenuation curves (TACs) of all ROIs were interpolated using cubic spline interpolation to improve temporal resolution as practiced with CTP TACs. 18 The TTP defined the TTP enhancement of the interpolated TAC. Delay was defined as the mean difference of all M2 TTP measurements to the averaged TTP measurements of the contralateral M2 segment.…”
Section: Dynamic Computed Tomography Angiography Image Analysismentioning
confidence: 99%
“…The time attenuation curves (TACs) of all ROIs were interpolated using cubic spline interpolation to improve temporal resolution as practiced with CTP TACs. 18 The TTP defined the TTP enhancement of the interpolated TAC. Delay was defined as the mean difference of all M2 TTP measurements to the averaged TTP measurements of the contralateral M2 segment.…”
Section: Dynamic Computed Tomography Angiography Image Analysismentioning
confidence: 99%
“…Recently, with a C-arm conebeam CT (CBCT) acquisition platform in the angiographic suite, the feasibility of acquiring dynamic CBCT perfusion (CBCTP) maps in the angiography suite has been demonstrated both in animals and in human subjects. 7,8 From the acquired CBCT perfusion dataset, time-resolved conebeam CT angiography (CBCTA) can also be generated to provide accurate diagnosis of large-vessel occlusions (LVOs). 9,10 In this study, we hypothesized that the use of timeresolved CBCTA would facilitate the evaluation of collateral status and clot burden in patients with AIS.…”
mentioning
confidence: 99%
“…If combined with faster and multiple rotations, it is possible to obtain cerebral blood flow with reasonable radiation exposure. 16 Because the arterial input function was determined by histogram rather than vessels, the measurements were relatively constant as long as most of the brain was included in the scanning range.…”
Section: Discussionmentioning
confidence: 99%
“…13 It can be used to access the extent of the ischemic core and detect hyperperfusion phenomena peritherapeutically in the angiography suite, facilitating endovascular therapy without the transfer of patients to the CT room. [10][11][12][13][14][15] In a recent study, Royalty et al 16 showed the feasibility of using C-arm CT to measure perfusion parameters in an animal model. Nevertheless, the combination of DSA and flat panel parenchymal blood volume raises concerns related to radiation exposure.…”
mentioning
confidence: 99%